O LUTO NO BRASIL NO FINAL DO SÉCULO XX - Pinheiro Koury, Mauro Guilherme (Caderno CRH, 2015)
Este artigo tem por objetivo contribuir para a compreensão das mudanças comportamentais da população brasileira urbana frente ao fenômeno do luto e da perda. É resultado de um grande mapeamento do comportamento do homem brasileiro, de segmentos médios urbanos, e das mudanças experienciadas na sua sensibilidade, no decorrer da segunda metade da última década do século XX, tendo o processo de luto e da perda como mote analítico. PALAVRAS-CHAVE: Trabalho de luto. Sentimento de perda. Sofrimento. Vergonha. Individualismo. Brasil urbano. MOURNING IN BRAZIL AT THE END OF THE 20TH CENTURY Mauro Guilherme Pinheiro Koury This article aims to contribute for the understanding of the behavioral changes in the urban Brazilian population regarding mourning and loss. It is the result of a broad mapping of the behavioral of Brazilians from average urban segments, and of the changes experienced in their sensibility during the second half of the 20th century, using mourning and loss as a guide for analysis. KEYWORDS: mourning, loss, bereavement, shame, individualism, urban Brazil. LE DEUIL AU BRÉSIL À LA FIN DU XXe SIÈCLE Mauro Guilherme Pinheiro Koury L’objectif de cet article est d’apporter une contribution à la compréhension des changements de comportement de la population brésilienne urbaine face au phénomène de deuil et de perte. Il résulte d’un quadrillage du comportement de l’homme brésilien, de segments de la classe moyenne urbaine, et des changements qui ont eu lieu au niveau de sa sensibilité au cours de la deuxième moitié de la dernière décennie du XXe siècle, le processus de deuil et de perte en constituant un attribut analytique. MOTS-CLÉS: Travail de deuil. Sentiment de perte. Souffrance. Honte. individualisme, Brésil urbain. <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;">